Dynamics of Islamic Law in Indonesia During the Reformation Period - Wildan Habib Azhari; Rasyid Siddiq; Zainul Fuad (Marga: Journal Of Innovation and Creatifity, 2024)
Since the people of the archipelago embraced Islam, Islamic law began to be applied in social life. The early era of Indonesian independence was the beginning of the enforcement and application of Islamic law in Indonesia, something that was visible in unwritten law, social practices, cultural practices, in legislation and in constitutional practice. After the change of regime, from the New Order to the Reformation era which began in 1998, it has brought major changes in various fields including the legal field. The debate between Islam and Pancasila has strengthened again. Based on the problems above, this article aims to explain three important things, including the dynamics between law and politics in Indonesia, then the development of Islamic law in Indonesia in the reform era, as well as factors that become opportunities and challenges for Islamic law amidst the plurality of national laws in the reform era. This research uses library research based on qualitative descriptive data about the history of the development of Islamic law.